2016
DOI: 10.18632/oncotarget.7456
|View full text |Cite
|
Sign up to set email alerts
|

Identity, proliferation capacity, genomic stability and novel senescence markers of mesenchymal stem cells isolated from low volume of human bone marrow

Abstract: Human bone marrow mesenchymal stem cells (hBM-MSCs) hold promise for treating incurable diseases and repairing of damaged tissues. However, hBM-MSCs face the disadvantages of painful invasive isolation and limited cell numbers. In this study we assessed characteristics of MSCs isolated from residual human bone marrow transplantation material and expanded to clinically relevant numbers at passages 3-4 and 6-7. Results indicated that early passage hBM-MSCs are genomically stable and retain identity and high prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 95 publications
2
30
0
5
Order By: Relevance
“…19 Although the underlying mechanisms remain unclear, previous reports have suggested that mitochondria, autophagy, genomic stability, and growth factor-mediated changes may affect MSC senescence as the cultivation time and passage number increase. 20,21 In addition, changes in stem cell phenotype may differ depending on the MSC origin, which could significantly impact their clinical potential. 22 Therefore, stemness must be considered before using MSCs for tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…19 Although the underlying mechanisms remain unclear, previous reports have suggested that mitochondria, autophagy, genomic stability, and growth factor-mediated changes may affect MSC senescence as the cultivation time and passage number increase. 20,21 In addition, changes in stem cell phenotype may differ depending on the MSC origin, which could significantly impact their clinical potential. 22 Therefore, stemness must be considered before using MSCs for tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was found that at early passages, human BM-MSCs are genetically stable and retain identity and high proliferation capacity, whereas cells became senescent at late passages. In parallel, the slower proliferation altered morphology and immunophenotype making them more susceptible to cell neoplastic formation concomitantly to a progressive decrease in clonogenicity and differentiation potential (Kundrotas et al 2016). MSCs derived from bone marrow of both murine and human origin have been widely investigated in experimental autoimmune encephalomyelitis (EAE), an induced model of MS.…”
Section: Bone Marrow-derived Mscsmentioning
confidence: 99%
“…[50][51][52][53] Mezenkimal kök hücreler kemik iliği, kordon kanı, trabeküler kemik ve adipoz dokulardan izole edilebilmektedir. [53][54][55] İn vitro ortamda adiposit, osteoblast ve kondroblastlara farklılaşma özellikleri bulunmaktadır.…”
Section: Mezenki̇mal Kök Hücreunclassified